O Rio Uruguai como estratégia de contextualização do ensino em uma escola com restrição de liberdade - Pessano, Edward Frederico Castro (2015)
Historically, the educational processes in restrictions units of freedom for minors have numberless problems relating to educational support and reintegration for teenagers, which varied authors have been expressed the lack of the effective implementation of the Partenereducative measures due do the inappropriate conditions of teaching education, lack of continued education for the teachers, as well as, the teenagers‟ lack of interest to continue studying even when released, besides the factories in the social and affective areas. In this sense, this research aimed to evaluate the aspects of educational processes in a unit of SocioEducational Assistance Foundation, checking the authors social profile, the unit routine, pedagogical aspects and strategies used in the unit, as well as, the implementation of the continued education program to the teachers, from the methodology of contextualize and the problematization, through the Maguerez‟ Arch and lastly, assess whether the implementation of a interdisciplinary school project based on Uruguay River as a educational contextualize theme may improve to the educational processes. Thus, the present study is a qualitative and quantitative research developed in the municipality of Uruguaiana in a school located within a unit of freedom restriction. The research is based on the teaching contextualize and problem solving, from the use of the Uruguai River as a theme focues to formal curricular contents of contextualize. The data analysis obtained in the diagnostic regarded the fragmentation of knowledge about the thematic broached, educational traditional strategies and less attractive to the students, besides low school interest. However, the continued education program made for the teachers demonstrated the acceptance, participation and interest of the group, which culminated with development and implementation of an educational proposal made by teachers and applied to the school with actions toward the elementary school. This proposal was entitled: “Uruguay River, a bed of Stories and Lives”, which was characterised by a class action strategy, interdisciplinary, contextualized and developed by teachers, who were the proposal leading players together with adolescents. The project's execution was accompanied by author's research, who acted as an instigator and facilitator of the process, registering, analyzing and evaluating the actions. At last, after all development and evaluation of this study with the results obtained it might have been possible to suggest that the methodology used allowed to establish a collective production process and a sharing of knowledge which culminated in the in the teachers professional improvement and internal restructuring of pedagogical work, stimulating actions and reflections that led to superation of some difficulties offered from the educational system, reflecting the improvement of the school perfomance indices.